Cardiovascular Disease and miRNAs: Possible Oxidative Stress-Regulating Roles of miRNAs - Seahyoung Lee (MDPI AG, 2024)
MicroRNAs (miRNAs) have been highlighted as key players in numerous diseases, and accumulating evidence indicates that pathological expressions of miRNAs contribute to both the development and progression of cardiovascular diseases (CVD), as well. Another important factor affecting the development and progression of CVD is reactive oxygen species (ROS), as well as the oxidative stress they may impose on the cells. Considering miRNAs are involved in virtually every biological process, it is not unreasonable to assume that miRNAs also play critical roles in the regulation of oxidative stress. This narrative review aims to provide mechanistic insights on possible oxidative stress-regulating roles of miRNAs in cardiovascular diseases based on differentially expressed miRNAs reported in various cardiovascular diseases and their empirically validated targets that have been implicated in the regulation of oxidative stress.